Internet of Things – Business – Marketing – Challenge - Tybura, Arkadiusz (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
The development of the Internet of Things (IoT), machines functioning independently in the network, seems unstoppable. Its enormous potential and dynamics are confirmed by numerous studies and reports indicating the intensive growth of both investment outlays and the value of the global IoT market. In addition, the involvement of big players such as Amazon, Google, Microsoft, Apple and Samsung proves that changes in the reality that surrounds us are becoming an irreversible trend. The entire economy is changing under the influence of the development of this technology. In fact, enterprises are the main beneficiaries of the progressing cybernetization, which allows, among other things, to: increase efficiency, improve quality, shorten delivery times, reduce production and service costs, or improve the use of information in the decision-making process. However, introducing innovative solutions always carries the risk of failure. The aim of the article was an attempt to identify the challenges related to the implementation of the Internet of Things in the sphere of business and marketing, which may constitute an obstacle in reaping the benefits offered by new technologies.